Finland Education Success - Subuh Anggoro; Ana Andriani; Ine Kusuma Aryani (Proceedings Series on Social Sciences & Humanities, 2023)
The success of Finnish education has been recognized worldwide and has become an interesting study material from planning to implementation. This paper explains how the Finnish education system starts from preliminary to higher education and the outputs and outcomes it produces.